(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
A comprehensive analysis was done to investigate the proximate, mineral, vitamin and phytochemical compositions of Ikom and Riverine cultivars of bitter leaf. The study was carried out using analytical procedures outlined by the association of official analytical chemists. The Riverine bitter leaf contained more moisture content (8.8%), crude fibre (8.5%), fat (2.8%) and ash (8.6%), while Ikom cultivar had more crude protein (27%), carbohydrate (51mg/100g) and dry matter content (94mg/100g). The Riverine bitter leaf contained more minerals; sodium (0.42%), phosphorus (27.87mg/100g), potassium (1.31%), iron (61.8mg/100g) and zinc (7.34mg/100g). While both cultivars had equal concentrates of calcium (3.8%) and magnesium (1.5%). The Ikom cultivar had more of Nitrogen (4.47%) and phosphorus (0.56%) This showed that they are good sources of minerals. The presence of more ash in riverine bitter leaf is a confirmation of the presence of more mineral elements. The riverine cultivar was relatively higher in all tested vitamins other than thiamine. The Riverine cultivar contained higher values of Flavonoids (4.29mg/100g), tannins (1.38mg/100g) and oxalates (0.086mg/100g) than the Ikom cultivar which had higher values of Alkaloids (3.61mg/100g), saponins (5.75mg/100g) and phenols (0.48mg/100g). The low alkaloids (mainly quinine) accounts for the slight bitter taste of the riverine cultivar. Generally, the two cultivars were rich in useful dietary nutrients, phytochemicals and antioxidants. It is recommended that more research be done to develop ways of multiplying the Riverine bitter leaf in rain forest and derived Savannah zones.